The quadratic formula is:
and ![\frac{-b - \sqrt{b^2 - 4ac} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%20-%20%5Csqrt%7Bb%5E2%20-%204ac%7D%20%7D%7B2a%7D)
In this case, a = 2, b = -3, and c = -7
So, we can plug in the numbers to get:
and ![\frac{-(-3) - \sqrt{(-3)^2 - 4(2)(-7)} }{2(2)}](https://tex.z-dn.net/?f=%5Cfrac%7B-%28-3%29%20-%20%5Csqrt%7B%28-3%29%5E2%20-%204%282%29%28-7%29%7D%20%7D%7B2%282%29%7D)
Simplifying, we get:
and ![\frac{3 - \sqrt{65} }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20-%20%5Csqrt%7B65%7D%20%7D%7B4%7D)
You need to use a calculator to find what these would be in decimal form. The answer, rounded to the nearest tenth, is: x = 2.8, x = -1.3